2006
DOI: 10.1158/0008-5472.can-05-3801
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 14-3-3σ as a Contributor to Drug Resistance in Human Breast Cancer Cells Using Functional Proteomic Analysis

Abstract: Multidrug resistance (MDR) is a major obstacle to successful cancer treatment. To understand the mechanism of MDR, many cancer cell lines have been established, and various mechanisms of resistance, such as ATP-binding cassette (ABC) transporter-mediated drug efflux, have been discovered. Previously, a MDR cell line MCF7/AdVp3000 was selected from breast cancer cell line MCF7 against Adriamycin, and overexpression of ABCG2 was thought to cause MDR in this derivative cell line. However, ectopic overexpression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(92 citation statements)
references
References 42 publications
5
86
0
1
Order By: Relevance
“…Similar findings have been reported for colorectal [19] and pancreatic cancers [35] and it has been postulated that 14-3-3σ over expression may be responsible for promoting proliferation and/or preventing apoptotic signal transduction [18]. Elevated 14-3-3σ expression has been reported as contributing to drug resistance in breast cancer cell lines [36], and its increased expression in the anaplastic cancer cell lines in the current study, may be able to explain, at least in part, the widespread resistance to chemo-therapeutic agents noted in this aggressive malignancy [37].…”
Section: Discussionsupporting
confidence: 82%
“…Similar findings have been reported for colorectal [19] and pancreatic cancers [35] and it has been postulated that 14-3-3σ over expression may be responsible for promoting proliferation and/or preventing apoptotic signal transduction [18]. Elevated 14-3-3σ expression has been reported as contributing to drug resistance in breast cancer cell lines [36], and its increased expression in the anaplastic cancer cell lines in the current study, may be able to explain, at least in part, the widespread resistance to chemo-therapeutic agents noted in this aggressive malignancy [37].…”
Section: Discussionsupporting
confidence: 82%
“…14-3-3 proteins control cell cycle, cell growth, survival, and apoptosis (38,39). In addition, 14-3-3j has been identified as a marker of potential clinical interest for breast cancer detection and contributes to drug resistance in human breast cancer cells (40). We also observed that two chaperones, Hsp60 and Hsp90h, which are heat shock proteins (37), are upregulated and subject to posttranslational modification, respectively.…”
Section: Resultsmentioning
confidence: 89%
“…Breast cancer cell lines with high PIK3CA-GS were confirmed to be resistant to rapamycin (69). (70) demonstrated that cell lines of human cancer which increased expression of 14-3-3σ contributed to drug resistance, suggesting that such a change is associated with clinical resistance to chemotherapy. In treatments stimulating apoptosis, ubiquitin and S100-A6 decreased in the lysates of breast cancer cell lines, and aberrant expression of the two proteins in breast cancer tissue was found (71).…”
Section: Prognostic and Predictive Marker Protein Profiling Studiesmentioning
confidence: 99%